Economic efficiency of hot water systems based on solar collectors - Клён, Андрей Николаевич; Ефременко, Виктория Викторовна (Technology audit and production reserves, 2015)
This paper focuses on the economic efficiency issues of the employment of hot water systems based on solarcollectors establishing in Ukraine. There have been determined the standard solutions to create hot water systems based on solar collectors. There have been calculated capitalized and current charges related with the launch and operation of these systems and the payback period. There have been analyzed the amount of energy produced by solar collectors of different power for water heating. As a result of the research conducted by the authors, they have reached a conclusion that the employment of hot water systems based on solar collectors is cost-efficient. Despite the high capitalized charges as compared to systems of electric and gas water heating they are compensated, on average, within 13-25 years. It is worth mentioning that one of the most important moments of such systems employment is not only their economic efficiency but also significant reduce of gas consumption in housing and utilities sector. This fact plays a fundamental role in ensuring the energy independence of Ukraine. The main deterrent restraining the mass employment of hot water systems based on solarcollectors in Ukrainian are sufficiently large initial expenses and lack of support on behalf of the state.